Comparison of Soft Tissue Changes Following Single-Jaw and Two-Jaw Orthognathic Surgery in Patients with Skeletal Class III Malocclusion (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to compare soft tissue changes observed in Class III skeletal deformity patients treated with either single-jaw surgery (mandibular setback via Bilateral Sagittal Split Osteotomy - BSSO) or two-jaw surgery (maxillary advancement via Le Fort I combined with mandibular setback via BSSO).Methods: A retrospective study was conducted on 40 treated Class III patients, divided into two groups based on the assigned surgical procedure: Group I underwent single-jaw surgery involving only mandibular setback (20 patients), and Group II underwent two-jaw surgery (20 patients).Results: Upper lip changes were observed in both groups, but the magnitude of change was significantly greater in the two-jaw surgery group. Patients in both groups showed marked improvement in facial soft tissue profiles, effectively correcting the concave facial appearance.Conclusion: When comparing soft tissue changes between Class III patients treated with single-jaw versus two-jaw surgery, significant differences were noted in specific parameters such as facial convexity, maxillary prominence, and upper lip prominence.
Keywords: Orthognathic surgery; Soft tissue; Skeletal Class III malocclusion.